1999
DOI: 10.1017/cbo9780511489846
|View full text |Cite
|
Sign up to set email alerts
|

Risk and 'The Other'

Abstract: From earthquakes to epidemics, AIDS to industrial accidents, the mass media continually bring into our daily lives the awareness of risk. But how do people respond to this increased awareness? How do people cope with living in what has been termed 'the risk society'? This book attempts to explain how, within a given social and cultural context, individuals make sense of impending crisis. In particular it tries to explain the phenomenon of a widespread sense of personal invulnerability when faced with risk: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
234
0
31

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 0 publications
5
234
0
31
Order By: Relevance
“…Participants identified that they were at risk from others within the healthcare setting, and regardless of education and understanding they are ultimately part of the wider population and their perceptions and the reality they constructed was influenced by external forces. However while participants saw the patients as 'others' who are vulnerable and the cause of disease (Joffe 1999) they also perceived a risk to themselves from these 'others' through contact with dirt, uncleanliness and the unknown. Distinct groups are identified from the data; self whose practice is rational or can be rationalized, and the 'others' who in this instance are both staff members and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Participants identified that they were at risk from others within the healthcare setting, and regardless of education and understanding they are ultimately part of the wider population and their perceptions and the reality they constructed was influenced by external forces. However while participants saw the patients as 'others' who are vulnerable and the cause of disease (Joffe 1999) they also perceived a risk to themselves from these 'others' through contact with dirt, uncleanliness and the unknown. Distinct groups are identified from the data; self whose practice is rational or can be rationalized, and the 'others' who in this instance are both staff members and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Joffe (1999) examines the issue of risk from the perspective of social psychology and looks at how experts, journalists and lay people make sense of the threat posed by epidemic diseases. Her analysis is based on Social Representations Theory (SRT) which attempts to methodically study individual and group 'common sense' knowledge, both in trying to discover what individual people think, and beyond that to what processes shape Representations of Mad Cow Disease.…”
mentioning
confidence: 99%
“…(Bauer and Gaskell 1999) In the case of new diseases, the link made between a new disease and previous ones is often made by an anchoring mechanism which integrates the understanding of a new disease by configuring it in terms of past epidemics. (Joffe 1999) For example: 'flu-like'; 'cousin of the common cold' and so on. Clearly though, the choice of anchor influences how serious the new disease is to be regarded.…”
mentioning
confidence: 99%
“…In the anthropologist Mary Douglas' accounts of pre-modern societies, risk simply means 'danger from future damage', with a community's construal of the dangers they face intimately linked to local cultural operations of morality, responsibility attribution and intergroup boundaries (Douglas, 1992;Douglas & Wildavsky, 1982). In contrast, contemporary usage of the term 'risk' implies precision of calculation, objectivity and control (Joffe, 1999). Viewing dangers in terms of causal, predictable relations is a distinctively modern phenomenon, swathing dangers in an aura of scientific measurement and control (Bernstein, 1998;Douglas, 1992).…”
Section: Challenging the Term 'Risk'mentioning
confidence: 99%
“…Buttressed by such findings, recognition of the limits of purely cognitive approaches appears to be dissipating further into the risk perception field: Twenty-five years after research began on the notion of 'optimistic bias' (Weinstein, 1978), a 'cognitive distortion' whereby people see themselves as less vulnerable to dangers than their peers, the psychologist who pioneered the concept has begun to change his take on what drives behaviour, shifting from the purely cognitive to the more emotive realm: "considerable evidence exists demonstrating that worry (a poorly defined concept containing elements of both emotion and attention) […] provides predictive power beyond that provided by judgements of likelihood and severity" (Weinstein, 2003, p. 48). Indeed, the very phenomenon of optimistic bias may be fundamentally emotionally driven, reflecting a defensive response to fear rather than 'cold' cognitive error (Joffe, 1999).…”
Section: Evidence For 'Risk Perception' Driving Action?mentioning
confidence: 99%